Formation of an ordered porous polymer microstructure by water droplet templating - Daly, Ronan (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
This thesis examines the complex system of competing mechanisms involved when evaporation of a polymer solution induces sufficient cooling to drive condensation of water droplets onto the solution surface, where they pack, order and are ultimately captured in a polymeric matrix as the solvent leaves. This use of rafts of water droplets to template a polymer solution leaves behind an ordered porous microstructured film of the polymer, upon evaporation of the water. The dynamic mechanism, rather than studied as a whole, was broken down into an examination of (i) the equilibrium force balance of droplets on the solvent surface and (ii) the dynamical behaviour associated with solvent evaporation, water condensation and the evolution of polymer solution concentration. The first section examines the interfacial energy balances that can ensure or prohibit stability of the water droplets at the solvent/air boundary. A theoretical model and a novel experimental approach are employed for a range of pure solvent systems. It is seen that standard techniques for defining a liquid lens is not sufficient to describe the water droplet stability observed at the interface, which leads to insights regarding the significant role of the three phase contact radius and its associated excess energy, the line tension. The second section examines the highly dynamic mechanisms involved in the templating of water droplets, focusing on the controlled and systematic change in ambient flow and humidity conditions while analysing both the physical response of the droplets, through optical microscopy, and the resulting change in the solution through in-situ mass and temperature readings developed specifically for this task. Coupling this controlled formation with a precise analytical technique to examine the cross-sections leads to the means and understanding to control the internal microstructure though dynamic tuning of the mechanism, resulting in a broad range of previously unreported porous architectures using this technique.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin